The interaction between visitations and child support transfers in non-intac households (2003)
Divorce negatively impacts children's welfare as a consequence of the reduction in monetary and time contributions of the non-custodial parent. In our framework parents constitute a bilateral exchange economy where the mother is endowed with control over visitations and the father has control over financial resources. Our results indicate that an endowment of equal time for both parents, reducing the time under the mother's control implies a reduction in the child support transfers from the father, and, therefore, a loss in the mother's consumption levels, A more equally shared time with the children increases the father's direct expenditures to the child, allowing the mother to spend less on child goods and partially compensating her consumption loss.